Optimization of Cultural and Physical Parameters for Phenol Biodegradation by Newly Identified Pseudomonas sp. AQ5-04 - Aisami, Abubakar; Yasid, Nur Adela; Shukor, Mohd Yunus Abd (Journal of Tropical Life Science, 2020)
Phenol is widely used by many industries and it is one of the highly toxicenviron-mental pollutants. Bioremoval is one of the most effective methods to remove phenol compared to other physio-chemical methods. Identification was carried out using 16s rRNA sequencing. Mineral salt media with 0.5 g/L phenol as the sole source of carbon. Factors influencing phenol degradation were optimised via one-factor-at-a-time and response surface methodology. Optimum degradation was achieved at pH 7.5, the temperature of 30°C and ammonium sulphate at 0.4 g/L. Using Response surface methodology the incubation period was reduced to 36 h compared to the OFAT approach where it takes 72 hours. The effect of 10 heavy metals at various concentrations was tested. The optimum values used for tempe-rature, pH, ammonium sulphate and salinity for both the OFAT and RSM have correlated with the only pH displayed the slighted difference of 7.0 for OFAT and 7.5 for RSM. This shows the closest optimum conditions for both methods. The strain is also resistance to some heavy metals usually found in polluted environ-ments together with phenol. Therefore, it can be clearly stated that Pseudomonas sp. strain AQ5-04 is the potential candidate for phenol bioremediation and further studies in the field of bioremediation. The bacterium can degrade phenol in the presence of between 1 to 3 ppm of the heavy metals As, Cd, Co, and Zn while growth and degradation were inhibited by Hg, Ag, Cu and Ni at 1 ppm. The isolate is a potential strain for further bioremediation studies.